College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 8 - Sequences, Induction, and Probability - Exercise Set 8.5 - Page 758: 34


See below

Work Step by Step

The binomial expression can always be rewritten as the following. $(A+B)^n = \sum _{k=0}^n C(n,r)* A^{n-r} * B^{r}$ Since we are finding the first 3 terms, we simply plug in the set $[0,1,2]$ $T_1 =C(9,0)*x^{9} =x^{9} $ $T_2 = C(9,1)*x^8*(-2y)=-18x^8y$ $T_3 =C(9,2)*x^7*4y^2= 144x^7y^2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.